Controlled synthesis of near-infrared quantum dots for optoelectronic devices. Issue 43 (26th October 2017) - Zhang, Hui; Selopal, Gurpreet S.; Zhou, Yufeng; Tong, Xin; Benetti, Daniele; Jin, Lei; Navarro-Pardo, Fabiola; Wang, Zhiming; Sun, Shuhui; Zhao, Haiguang; Rosei, Federico
Abstract : We designed a facile approach for the synthesis of PbS quantum dots using thiourea and lead acetate as sources of sulfur and lead, respectively. Abstract : We designed a facile approach for the synthesis of PbS quantum dots (QDs) using thiourea and lead acetate as sources of sulfur and lead, respectively. The sizes of the PbS QDs could be systematically controlled by simply adjusting the reaction parameters. Cd post-treatment via a cation exchange method was performed to increase the stability of QDs. As a proof of concept, colloidal PbS QDs synthesized by using air-stable thiourea were employed as light harvesters for both (i) solar driven photoelectrochemical (PEC) hydrogen generation and (ii) QDs sensitized solar cells (QDSSCs). For PEC hydrogen generation, similar saturated photocurrent densities are observed by using thiourea compared to bis(trimethylsilyl) sulfide, which is air-sensitive and unstable. For QDSSCs, the devices fabricated with QDs synthesized from thiourea reveal a better performance compared to devices fabricated with QDs synthesized from traditional bis(trimethylsilyl) sulfide. Our work demonstrates that this synthetic method is a promising alternative to the existing methodologies of PbS QDs and holds great potential for future solar technologies.